Assessment of Small C-Fiber Status for Screening of Oxidative Stress in Patients at Risk of Diabetes - Parfentyeva, E.; Saha, S.; Hjellset, V. T.; Kopprasch, S.; Schwarz, P. E. H. (Hormone and Metabolic Research, 2014)
Oxidized LDL (oxLDL), anti-oxLDL antibody (anti-oxLDL) and paraoxonase (PON1) are increasingly being reported to be associated with diabetic atherosclerosis. Oxidative stress could affect also small C-fibers innervating the sweat glands even in prediabetes. Hence it could be hypothesized that sweat dysfunction may be a predictor of oxidative stress status for early detection of diabetes. Ezscan, a new device, has recently been developed to measure the sweat function. Therefore, this study was aimed to determine the relevance of this Ezscan method to identify impairment in oxidative stress parameters. Plasma levels of oxLDL and anti-oxLDL were measured by enzyme immunoassay and ELISA respectively. Small C-fiber status was assessed by measurement of hand and foot sweat function with the help of Ezscan device and subsequent calculation of a risk score. Out of 82 subjects recruited in this study, 38 had impaired glucose tolerance and 6 had newly diagnosed diabetes mellitus. Ezscan risk score was significantly (p=0.004) correlated with oxLDL/anti-oxLDL ratio (0.32). Area under the curve (AUC) of receiver operating characteristics (ROC) analysis for detection of oxLDL/anti-oxLDL ratio (>0.12) was 0.76. For an Ezscan risk score of 50%, the sensitivity and specificity were 68% and 71% respectively. After adjustment for age and BMI, PON1 activity showed significant difference among the 3 risk groups defined by Ezscan risk score. Based on these results it may be concluded that Ezscan could be a useful screening tool in daily practice to assess alterations in oxidative stress parameters in individuals at risk of developing diabetes.
Keywords: sweat dysfunction; oxidized LDL; antioxidized LDL antibody; paraoxonase; atherosclerosis